2019
DOI: 10.1093/rfs/hhz080
|View full text |Cite
|
Sign up to set email alerts
|

Do CEOs Affect Employees’ Political Choices?

Abstract: We study the relation between CEO and employee campaign contributions and find that CEO-supported political candidates receive 3 times more money from employees than candidates not supported by the CEO. This relation holds around CEO departures, including plausibly exogenous departures due to retirement or death. Equity returns are significantly higher when CEO-supported candidates win elections than when employee-supported candidates win, suggesting that CEOs’ campaign contributions are more aligned with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Finally, poor fit with the organisation provoked by misaligned ideologies can also lead to higher turnover (Chatterji and Toffel, 2015; Leak et al , 2015; Brown et al , 2020). Babenko et al (2020) found higher turnover rates when employees donated to political candidates not supported by the corporation’s CEO.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Finally, poor fit with the organisation provoked by misaligned ideologies can also lead to higher turnover (Chatterji and Toffel, 2015; Leak et al , 2015; Brown et al , 2020). Babenko et al (2020) found higher turnover rates when employees donated to political candidates not supported by the corporation’s CEO.…”
Section: Resultsmentioning
confidence: 97%
“…Most studies account for moderation based on recipients’ (mis)alignments (Hambrick and Wowak, 2021). This could be because their political and personal values diverge from general ideological beliefs (Leak et al , 2015), because of political engagement (Babenko et al , 2020) or in response to symbolic value systems (Melloni et al , 2019; Brown et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations